2020
DOI: 10.1111/1745-9133.12489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of defelonizing drug possession on recidivism

Abstract: sought to scale back punishment for selected drug and property offenses, making them misdemeanors rather than felonies. Although others have examined the impacts of Proposition 47 on crime rates, here we examine the impacts on a range of recidivism outcomes specifically for individuals convicted for drug possession offenses. We focus on the defelonization of drug possession because nationally evidence suggests that public and policy maker sympathy for reducing incarceration use is greatest for nonviolent drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…With the penalty reduction for the specified offenses, law enforcement officers seemed to experience a proportional reduction in the motivation to arrest offenders (Bird, Nguyen, & Grattet, 2020;Grattet et al, 2017). These results may seem to align with the voters' wishes since they passed Proposition 47 with a 60% vote (Austin, 2016).…”
Section: Social Implicationsmentioning
confidence: 85%
See 2 more Smart Citations
“…With the penalty reduction for the specified offenses, law enforcement officers seemed to experience a proportional reduction in the motivation to arrest offenders (Bird, Nguyen, & Grattet, 2020;Grattet et al, 2017). These results may seem to align with the voters' wishes since they passed Proposition 47 with a 60% vote (Austin, 2016).…”
Section: Social Implicationsmentioning
confidence: 85%
“…Those crimes that California law previously listed as felonies now became reclassified as misdemeanors. Since the associated penalties and enforcement options gave law enforcement officers further discretion, behaviors were apt to change as well (Bird, Nguyen, & Grattet, 2020). Knowing how law enforcement officers respond to similar amendments in the law is crucial to understanding police officer decision processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the maximum allowable punishment could help reduce gender disparities. Prior policy-evaluation studies show how scaling back charging and punishment codes, even when implemented in a race-neutral manner, can reduce the magnitude of racial disparities in incarceration without significantly increasing recidivism (Bird et al, 2020; Lofstrom et al, 2020; MacDonald & Raphael, 2020). Logically, we would expect a similar narrowing of the gender gap in punishment in response to efforts to scale back severity by censoring the top end of possible punishment.…”
Section: Discussionmentioning
confidence: 99%
“…The results are persistent with the previous study of Hasisi, Carmel, and Wolfowicz (2020) who showed that social factors for example labeling and negligence from others increase recidivism. Moreover, helplessness (Bird, Nguyen, & Grattet, 2020), bad relationship with neighbors, (Akporaro, 2019), labeling (Barrick et.al, 2014), grouping (Onifade et. al, 2008), patriarchy (Lutzee & Bell, 2005), and negligence from authorities (Walters et.al, 2011) lead a person towards recidivism.…”
Section: Discussionmentioning
confidence: 99%